VGLL fusions define a new class of intraparenchymal central nervous system schwannoma - Schmid, Simone; Mirchia, Kanish; Tietze, Anna; Liu, Ilon; Siewert, Christin; Nückles, Jakob; Schittenhelm, Jens; Behling, Felix; Snuderl, Matija; Hartmann, Christian; Brandner, Sebastian; Paine, Simon M.L.; et al. (Neuro-Oncology, 2025)
BACKGROUND: Intracerebral schwannomas are rare tumors resembling their peripheral nerve sheath counterparts but localized in the central nervous system (CNS). They are not classified as a separate tumor type in the 2021 World Health Organization classification. This study aimed to compile and characterize these rare neoplasms morphologically and molecularly. METHODS: We analyzed 20 tumor samples by histology, RNA next-generation sequencing, DNA-methylation profiling, copy number analyses, and single-nucleus RNA sequencing (snRNA-seq). Clinical data, including age, sex, and disease progression, were collected. Magnetic resonance imaging (MRI) series were included when available. RESULTS: All cases with tissue available for histology review (n = 13) were morphologically consistent with intracerebral schwannoma, but differed in their extent of glial fibrillary acidic protein staining. All (n = 20) shared DNA-methylation profiles distinct from other CNS tumors, as well as from Vestigial-like family (VGLL)-altered peripheral nerve sheath tumors. Most cases (n = 14/17) harbored fusions of either Vestigial-like family member 3 (VGLL3) or Vestigial-like Family member 1 (VGLL1) (CHD7::VGLL3 [n = 9/17] and EWSR1::VGLL1 [n = 5/17]). In 2 cases, the presence of a VGLL3 fusion was also confirmed by copy number analyses (n = 2/17). MRI (n = 4) showed well-defined, nodular tumors with strong, homogeneous enhancement and no diffusion restriction. Tumors were located throughout the neuroaxis (supratentorial [n = 15], infratentorial [n = 4], and spinal [n = 1]). snRNA-seq of a VGLL1-fused tumor indicated VGLL1 upregulation in 28.6% of tumor cells (n = 1). During a median follow-up of 1.8 years (range 3 months-9 years), none of the tumors recurred (n = 10). CONCLUSIONS: We identify and define a new benign tumor class, designated VGLL-altered intraparenchymal CNS schwannomas. These tumors feature VGLL alterations and a specific DNA-methylation profile, with schwannoma-like histopathology and CNS localization, akin to previously classified intracerebral schwannomas.
CRIS-Team Scopus Importer:2025-05-30
Keywords: gliofibroma; glioma; schwannoma; tumor; VGLL